ANALISIS FAKTOR BIOLOGI DAN SOSIAL TERHADAP PRODUKSI KOPI ROBUSTA DI NAGARI TALAO SUNGAI KUNYIT KECAMATAN SANGIR BALAI JANGGO KABUPATEN SOLOK SELATAN - Murnita, Murnita; Putri Yuli Anti; Herda Gusvita (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2026)
The amount of Robusta coffee production must continue to be increased to meet market demand. Farmers undergo a production process supported by various production factors. The purpose of this study was to determine how much Robusta coffee is produced and to analyze the biological and social factors that influence the production of this coffee in Nagari Talao Sungai Kunyit, Sangir Balai Janggo District, South Solok Regency. This research was conducted from August 5 to September 5, 2024. The method used in this study was quantitative descriptive, with a population of 36 farmers from a total of 65 Robusta coffee farmers. For data analysis, researchers used multiple linear regression analysis with the Cobb Douglas model. The findings of this study indicate that the total production of Robusta coffee in Nagari Talao Sungai Kunyit by 36 farmers reached 35,587 kg, with an average production per farmer of 988.53 kg and an average per hectare of 754.60 kg. Biological factors that have a significant influence on Robusta coffee production in the area are the number of plants, the amount of fertilizer, and the amount of pesticide. However, land area and social factors such as the number of workers did not show a significant influence on Robusta coffee production in Nagari Talao Sungai Kunyit.